Single versus double flap approach in periodontal regenerative treatment. (29th May 2015) - Schincaglia, Gian Pietro; Hebert, Eric; Farina, Roberto; Simonelli, Anna; Trombelli, Leonardo
Abstract Aim to compare the outcomes of a regenerative strategy based on recombinant human platelet‐derived growth factor–BB (rhPDGF‐BB, 0.3 mg/ml) and β‐tricalcium phosphate (β‐TCP) in the treatment of intraosseous defects accessed with the Single Flap Approach (SFA) versus Double Flap Approach based on papilla preservation techniques (DFA). Materials and Methods Fifteen and 13 defects, randomly assigned to SFA or DFA, respectively, were grafted with rhPDGF‐BB + β‐TCP. Probing parameters were assessed before and 6 months after surgery. Pain (VASpain) was self‐reported using a visual analogue scale. Results Twelve SFA sites and DFA 6 sites showed complete flap closure at 2 weeks post‐surgery. No significant differences in 6‐month changes in probing parameters and radiographic defect fill were found between groups. Significantly lower VASpain was observed in SFA group compared to DFA group at day +1, +2 and +6. A significantly greater number of analgesics were consumed in the DFA group compared to the SFA group at day +1. Conclusions When combined with rhPDGF‐BB and β‐TCP, the SFA may result in similar clinical outcomes, better quality of early wound healing, and lower pain and consumption of analgesics during the first postoperative days compared to the DFA.